Intrauterine growth restriction: distribution, risk factors, management of labour and outcome - Andzane, Diana; Gapatins, Igor; Miskova, Anna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The development of Intrauterine growth restriction (IUGR) determines maternal, fetal and placental factors. Many of these factors are preventable. There is still no enough developed effective pregnancy and labour management tactics that could protect both mother and child from the unintended consequences. Methods: The research was made in Riga Maternity Hospital. In the research there were included pregnant women who gave birth neonates with weight under 10th percentile (IUGR group) as well there was compiled the control group. The weight of neonates was evaluated using the percentile scales - Intrauterine Growth Curves based on US data. Results: According to the criteria, in the IUGR group were included 209 pregnant women and in the control group was the same number of patients. In the IUGR group mothers discharged from the hospital one day later than it was in the control group both after vaginal delivery (4.0 ± 1.5 vs. 3.3 ± 1.0, p˂0.0001) and after caesarean (5.6 ± 1.5 vs. 4.5 ± 1.0, p=0.0001). Comparing the evaluations after Apgar scale after spontaneous birth, induced labour and caesarean it was discovered that there is no statistically significant difference. Conclusions: IUGR negatively affect not just the fetus but also the mother and this is the reason why she should stay in the hospital for a longer period due to the child or experience the caesarean.